Phylogenetics and systematics of Eria and related genera (Orchidaceae: Podochileae). (25th January 2018) - Ng, Yan Peng; Schuiteman, AndrÉ; Pedersen, Henrik Æ; Petersen, Gitte; Watthana, Santi; Seberg, Ole; Pridgeon, Alec M; Cribb, Phillip J; Chase, Mark W
Abstract: A phylogenetic hypothesis for tribe Podochileae with emphasis on subtribe Eriinae s.s. is based on nucleotide sequences of the nuclear ITS and four plastid regions ( matK, trnL-F spacer, trnL intron and ycf1 ). The strict consensus tree based on parsimony is largely congruent with the maximum likelihood tree with a few major differences; most importantly, monophyly of Podochileae as recently circumscribed is strongly supported by the maximum likelihood tree but not recovered in the parsimony analysis. Monophyly of Thelasiinae s.s. (without Ridleyella ) and Eriinae s.l. (including Podochilinae) is supported, whereas Eria s.l. appears polyphyletic. The generic circumscription of Eriinae s.s. (excluding Podochilinae) is revised, and 21 genera are accepted, including two not previously recognized. Nomenclatural changes and a key to genera in Eriinae are provided.